Critical Thinking in EFL Academic Writing: Influencing Factors and Strategic Approaches - Fajaryani, Nunung; Abrar, Mukhlash; Yeni, Fitria; Failasofah, Failasofah; Heryanti, Reny (Edukasi, 2025)
Critical thinking is defined as a pivotal role in students' academic writing process, but in practice, the application of this skill often becomes quite a complex challenge for students as they formulate new ideas, analyse, evaluate, and synthesize information, and finally draw conclusions. Therefore, this study was conducted to explore the factors that influence EFL students' abilities and to investigate the strategies they use to develop critical thinking skills in academic writing, especially seventh-semester students majoring in English at a public university in Jambi. This study used a qualitative approach with a case study design. Data were gathered by using semi-structured interviewed with ten students. The researchers examined and interpreted the data collected using Braun and Clarke's stages of thematic analysis. The research findings indicate that EFL students face several factors that affect their ability to develop critical thinking in academic writing. These factors include personal competence issues such as a lack of topic knowledge, linguistic challenges, including difficulties with grammar and vocabulary; and psychological barriers, such as low motivation, lack of self-confidence, and anxiety during supervision. Despite these challenges, EFL students employ various strategies to overcome obstacles in developing critical thinking skills. These strategies include self-management, the use of technological support, cultivating a conducive learning atmosphere, leveraging support systems, and managing tutoring schedule effectively.